Bovine lactogenic immunity against cholera toxin-related enterotoxins and Vibrio cholerae outer membranes. - Boesman-Finkelstein, M (Infect Immun, 1989)
The newly parturient cow secretes large quantities of immunoglobulin G1, a relatively protease- and heat-resistant immunoglobulin, in its colostrum and milk. This study establishes the feasibility of producing protective colostral immunoglobulins by immunizing pregnant cows with cholera toxin (CT), a CT-related enterotoxin from Escherichia coli, and Vibrio cholerae outer membranes (OMs). The OMs were prepared from bacteria grown under iron-replete or iron-deficient (to simulate the in vivo environment) conditions. Immunoglobulins were purified from the colostrum of newly parturient control and immunized cows. The bovine anti-CT and anti-H-LT (CT-related heat-labile enterotoxin produced by diarrheogenic E. coli strains of human origin) antibodies were quantitated by enzyme-linked immunosorbent assays and by neutralization of toxin activity in both Y-1 adrenal cell and infant rabbit assays. The bovine anti-OM antibodies from both high-iron-grown and low-iron-grown vibrios were assessed by bacterial agglutination and by Western blot (immunoblot) analysis of polyacrylamide gel electrophoresis of high-iron-grown and low-iron-grown OMs. To test their protective effect, immunoglobulin preparations were administered orally in infant feeding formula to 6-day-old rabbits. Anti-CT and anti-OM immunoglobulins elicited statistically significant protection against diarrhea in infant rabbits challenged intraintestinally with virulent cholera vibrios. IMAGES: